Privity of contract in international investment arbitration original sin or useful tool? - Magnarelli, Martina (International arbitration law library ;, 2020)
Privity of Contract in International Investment Arbitration' elaborates in detail on the interpretation and application of the doctrine of privity of contract to investment treaty disputes. At least on one occasion privity of contract (or the lack of it) has been described as an "original sin" for international investment arbitration. Privity of contract essentially means that a subject must be a party to a contract, to acquire rights and assume obligations, to sue and be sued under that contract. But is privity of contract the reason why investor-state dispute settlement (ISDS) is open to criticisms, or could it contribute to solving the system's legitimacy crisis? Arbitral tribunals often need to decide whether they have jurisdiction in cases where a party to the investment contract is not the claimant but a related entity, or not the central government, but a state agency or state-owned enterprise. In light of the deep interconnection between, on the one hand, the criticism surrounding investment treaty arbitration, be it judicial activism and regulatory chill or abuse of law and indirect claims - and, on the other hand, the domains where privity of contract applies, this book's original and far-reaching analysis comprehensibly lays out a possible use of the doctrine that can contribute to leading ISDS out of the crisis.